Handbook of research on international strategic management (Cheltenham, 2012)
"Leading thinkers about the multinational enterprise offer both concise syntheses and critical reflections of the state of the art on international strategic management research. They in particular highlight the potential of internalization theory as a central paradigm for the field, and critically examine pertinent issues such as the complex notion of distance in international business. Refreshingly, they do not shy away from naming flaws in recent work, while offering avenues to improve the quality and impact of future research.’